STUDY OF THE EMOTIONAL COMPONENT OF PRIMARY SCHOOL CHILDREN VALUE ATTITUDE TO ECOLOGICAL SITUATIONS OF THE REGION - Solovyeva, Tatiana; Vitkovskaya, Irina; Ovchinnikova, Alexandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Unfavorable forecasts of environmental scientists regarding environmental changes actualize the problem of environmental values importance in the process of children upbringing.The article theoretically substantiates that emotions caused by perception of ecological situations of their region leave unconscious "imprints" in the child's life and therefore can serve as a psychological foundation for the formation of these values in primary school children. For children of primary school age, when they assess environmental situations, circumstances, events they encounter in their lives, the emotional reaction often outstrips the cognitive one, reflects the personal meaning, value attitude of a child towards them.The aim of the article is to study the emotional component of primary school children’ value attitude to the ecological situation of his region in order to introduce core value of "ecological safety" into his/her system of values. The study was based on the analysis of philosophical, psychological and pedagogical literary sources, testing, interviewing primary school children and pedagogical experiment.Managing the emotional development of primary schoolchildren can significantly change their value attitude to nature. Under conditions of the experiment, 61% of children began to realize their need for vigorous activity, and 17% of junior schoolchildren became psychologically ready for joint environmental protection activities.